(untitled) (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2019)
The Qur’an describes humans as biological, psychological and social beings. All three dimensions must be integrally integrated within human beings. No one can dominate the other. Like, his tendency as a biological creature is more prominent than his psychological dimension. The human dimensions depicted in the Qur’an also show that humans have diverse needs. As a biological creature, man needs things that can be healthy and protect his body. As human psychological beings need things that can nourish their intellectual and spiritual growth. As social beings humans need to socialize with other creatures.